2015
DOI: 10.1159/000381747
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy in Children with Myelomeningocele: A Case Series

Abstract: Hydrocephalus develops in up to 80-90% of children with myelomeningocele (MM) after closure of the defect. Traditionally, ventriculoperitoneal shunts have been used to manage hydrocephalus in these patients. A role for endoscopic third ventriculostomy (ETV) in MM has provoked much debate, principally due to anatomical variants described, which may complicate the procedure. We present 7 cases of children with MM and hydrocephalus undergoing a total of 10 ETV procedures. All patients demonstrated clinical improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Although the incidence of MAH at birth is 15 to 20%, it increases up to 80 to 90% after the closure of the defect (10). However, the exact etiology of MAH still remains unclear.…”
Section: █ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the incidence of MAH at birth is 15 to 20%, it increases up to 80 to 90% after the closure of the defect (10). However, the exact etiology of MAH still remains unclear.…”
Section: █ Discussionmentioning
confidence: 99%
“…Kulkarni et al (6) reported that the incidence of complications such as new neurological deficit or meningitis was less than 2%. Although the recent development of ETV has provided a challenging way of treatment, it still has a very limited role in the first-line treatment of MAH patients due to the immature CSF reabsorption system and anatomical difficulties in these patients; therefore, this method should be suggested only in selected cases (3,10).…”
Section: █ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From papers we identified, the reported success rates for ETV as a primary treatment ranged from 29% to 37.5%, whereas success rates for ETV after shunt failure ranged from 50% to 92%. 22,46,50,54 Long-term ETV outcomes after 5 years follow-up demonstrated ETV success rates of 53.3% and 64.3% when used as a first or second treatment modality, respectively. 53 Long-term neurocognitive outcomes between ETV and VPS groups are similar.…”
Section: Etvmentioning
confidence: 99%